Report on professional attachment with Diong T. P. & Co. - Ng, Cheryl Siew Chern. (2008)
This report is intended to document the job scope of the duties performed during the course of attachment, paying special attention to several key areas that are most stimulating. In addition, conclusions will be drawn and recommendations made.